Antimicrobial activity of bioactive materials - Emerenciano Bueno, Carlos Roberto [UNESP]; Cosme-Silva, Leopoldo [UNESP]; Benetti, Francine [UNESP]; Dezan-Júnior, Elói [UNESP]; Angelo Cintra, Luciano Tavares [UNESP]; Duarte, Paulo Carvalho Tobias [UNESP]; De Castilho Jacinto, Rogério [UNESP] (My University, 2019)
Bacteria are observed in the entire human body. When colonizing or forming biofilm in the oral cavity, may lead to primary, persistent or recurrent infections, resulting in destruction of dental hard and soft tissues. Since in health sciences, decreasing or eliminating bacterial levels is directly related to success, there has been a continuous effort to increase antimicrobial properties of biomaterials used for different purposes. Antimicrobial activity refers to the process of killing or inhibiting bacterial growth. Thus, an antibacterial bioactive material has the ability to kill bacteria or suppress growth or their ability to proliferate, by stimulating the host living tissues to produce an unfavorable environment. For over 100 years, antimicrobial properties referred to the ability to kill bacteria in a planktonic phase. However, almost all bacteria live in biofilm, which is an orientated aggregation of microorganism enclosed in extracellular polymeric substance, increasing resistance 1,000 to 1,500 times in comparison to their resistance in planktonic phase. This paradigm change led researches to improve bacteriology tests, incorporating the antibiofilm concept to the antimicrobial activity. Since the understanding of the biofilm functioning, the improvement of bacterial tests has become paramount. In dentistry, a wide range of dental materials used in cariology, endodontics, restorative dentistry and periodontology shows improved antibacterial ability, compared to earlier generations. According to the literature, the key of antimicrobial effects of bioceramic dental materials is directly related to the biomineralization ability, induced by calcium silicates/phosphates components. Up to this date, literature shows that bioactive materials, such as MTA-based cements, have antibacterial and antifungal effect, due to their basic components. However, despite the large number of reported satisfactory antimicrobial results, constant research is needed to continue improving the performance of those materials in dental practice, and to assess the newly introduced materials, regarding their different compositions and consistencies. This chapter discusses bacteria and biofilm characteristics along with the main antimicrobial activity mechanism of bioactive ceramics used in dental research.
Keywords: Antibacterial activity; Antibiofilm activity; Bacteria; Bioactivity; Biofilm